2019
DOI: 10.1161/hypertensionaha.118.12048
|View full text |Cite
|
Sign up to set email alerts
|

High Systolic Blood Pressure Induces Cerebral Microvascular Endothelial Dysfunction, Neurovascular Unit Damage, and Cognitive Decline in Mice

Abstract: A chronic and gradual increase in pulse pressure (PP) is associated with cognitive decline and dementia in older individuals, but the mechanisms remain ill-defined. We hypothesized that a chronic elevation of PP would cause brain microvascular endothelial mechanical stress, damage the neurovascular unit, and ultimately induce cognitive impairment in mice, potentially contributing to the progression of vascular dementia and Alzheimer disease. To test our hypothesis, male control wild-type mice and Alzheimer dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 42 publications
5
87
1
Order By: Relevance
“…Experiments were performed in male wild-type mice at 6 months old (WT6: n = 4), transgenic Amyloid Precursor Protein Presenilin-1 (APP/PS1) mice at 6 months old (AD6: n = 4), and APP/PS1 mice at 6 months old for which voluntary exercise was initiated at 3 months old (AD6&EX: n = 4). Previous work showed a clear onset of cognitive symptoms in APP/PS1 mice at 4.5 months old (Cifuentes et al, 2015) and established at 6 months old (de Montgolfier et al, 2019), and thus, we conducted imaging at 6 months old and investigated the hemodynamic changes in this relatively early stage of AD. For the AD6&EX group, exercise was voluntary.…”
Section: Experimental Designmentioning
confidence: 99%
“…Experiments were performed in male wild-type mice at 6 months old (WT6: n = 4), transgenic Amyloid Precursor Protein Presenilin-1 (APP/PS1) mice at 6 months old (AD6: n = 4), and APP/PS1 mice at 6 months old for which voluntary exercise was initiated at 3 months old (AD6&EX: n = 4). Previous work showed a clear onset of cognitive symptoms in APP/PS1 mice at 4.5 months old (Cifuentes et al, 2015) and established at 6 months old (de Montgolfier et al, 2019), and thus, we conducted imaging at 6 months old and investigated the hemodynamic changes in this relatively early stage of AD. For the AD6&EX group, exercise was voluntary.…”
Section: Experimental Designmentioning
confidence: 99%
“…For instance, animal models of chronic cerebral hypoperfusion show white matter lesions and cognitive impairment, but do not correspond well to the cardiovascular mechanisms of VCI. To make up for this drawback, animal models of cardiovascular diseases such as heart failure (transverse aortic constriction model [21][22][23][24], myocardial infarction model [25]), hypertension (stroke prone spontaneously hypertensive rat model [26,27], chronically hypertensive rhesus monkey model [28]), atherosclerosis (Apolipoprotein E knockout mouse model [29,30], low-density lipoprotein receptor-knockout mouse model [31]), and embolic models [32,33] are essential for a deeper understanding of vascular dementia in humans [17,18]. Figure 1.…”
Section: Pathogenetic and Neurobiological Mechanism Of Subcortical Vamentioning
confidence: 99%
“…Epidemiological studies in individuals with AD or in the elderly identified vascular complications associated with peripheral or brain diseases as risk factors for AD (Breteler 2000;de la Torre 2002). Altogether, this suggests that cognitive decline may be unveiled by brain vascular abnormalities and in particular brain microvascular abnormalities (de la Torre 2002;de Montgolfier et al 2019;Zlokovic 2002).…”
mentioning
confidence: 97%